(untitled) (Global Journal of Human-Social Science, 2020)
The strategic management of agricultural enterprises is to create conditions and develop mechanisms for the sustainable development of the enterprise, providing employment and income for the rural population. Diversification strategies are an integral part of the enterprise’s corporate strategies, namely, growth strategies that allow, firstly, to determine the direction of development of the enterprise in accordance with market requirements, and secondly, the availability of its own resources and the appropriateness of external acquisitions. The article analyzes the regional features of agricultural production in the Republic of Karakalpakstan. The Republic of Karakalpakstan is divided into 4 conditional zones and the current market conditions for agricultural products and food are also analyzed. The degree of saturation of regional markets with agricultural products was studied. The country’s selfsufficiency in main agricultural products are determined. Based on the analysis, proposals and recommendations for the development of each zone were developed.